2020
DOI: 10.1299/jamdsm.2020jamdsm0023
|View full text |Cite
|
Sign up to set email alerts
|

A modular design strategy considering sustainability and supplier selection

Abstract: To utilize the residual value, which remains an idle asset and disposed product based on the circular economy package, the definition or clarification of such a value and the development of a scheme for such a reutilization is essential. In addition, to facilitate an efficient utilization of the residual value, a product or its components needs to be designed considering its future reuse, remanufacturing, and upgrading. When companies monitor product usage using the Internet of things, they can make proposals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
5
0
4
Order By: Relevance
“…Inoue, M.; Yamada, S.; Miyajima, S.; et al [42] Proposes a modular design and a strategic evaluation method based on the viewpoint of supply chain management considering sustainability and supplier selection simultaneously. The proposed method evaluates the designed modular strategy from the perspectives of cost, environmental load in production and transportation, quality, and procurement lead time.…”
Section: Author (Year) Study Objective Case Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Inoue, M.; Yamada, S.; Miyajima, S.; et al [42] Proposes a modular design and a strategic evaluation method based on the viewpoint of supply chain management considering sustainability and supplier selection simultaneously. The proposed method evaluates the designed modular strategy from the perspectives of cost, environmental load in production and transportation, quality, and procurement lead time.…”
Section: Author (Year) Study Objective Case Focusmentioning
confidence: 99%
“…In addition, the Engineering, Manufacturing, and Mechanical knowledge domains are presented, for example, at the research of modular design and a strategic evaluation method considering sustainability and supplier selection [42], as observed at (a) clusters one (red) and (b) four (yellow); and at the investigation about the decision support model for economical material-based carbon recovery [43], as observed at (c) clusters one (red) and (d) three (blue). Regarding the Green and Sustainable Science knowledge domains, the subject of the studies are business models for re-distributed manufacture employing additive manufacturing [47], as observed at (e) clusters two (green) and (f) four (yellow), and other research is related to the usage-focused servitized business model [35], as observed at (g) cluster four (yellow).…”
Section: Terms Map Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Pandey et al have applied DSM in an effort to assess remanufacturability and incorporate this at the design stage [44]. In a recent effort, Inoue et al proposed a DSMbased design method focused on sustainability in which ensuring remanufacturability as a key focus [45].…”
Section: Applications Of Design Structure Matrix To Remanufacturing A...mentioning
confidence: 99%
“…パターンの確保が挙げられており,従来の大量生産,大量消費,大量廃棄の社会からの脱却が求められている. この実現のためには,生産者が資源の投入,製品の生産・使用の段階だけでなく,廃棄物等となった後まで一定 の責務を負う拡大生産者責任(EPR)という考え方やエコデザインの考えを先進国が発展途上国に普及させてい くことが重要である(環境省, 2017) .現在,多くの企業がリマニュファクチャリング (Masui, 2009)やアップグ レード (Yamada, S. et al, 2016(Yamada, S. et al, , 柴田他, 2017 などの環境配慮設計や, 環境にやさしい製品開発 (Bracke et al, 2017) , 持続可能性のためのサプライチェーンの構築 , Inoue et al, 2020…”
unclassified